Development of EEG-based stress index - Norizam, Sulaiman; Mohd Nasir, Taib, Prof. Dr.; Sahrim, Lias; Zunairah, Hj Murat; Siti Armiza, Mohd Aris; Mahfuza, Mustafa; Nazre, Abdul Rashid (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/